Herding Behavioral Motivation conducted by Coronial Investors: Study on Indonesian Stock Exchange’s - Nuranyanto, Akhmad; Raharja, Surya (Department of Management, Faculty of Economics and Business, Universitas Negeri Semarang, 2024)
The objective of this research is to determine whether periods of market down- turn are accompanied by herding behavior among investors. During the Covid-19 pandemic, not only the stock market but also the number of investors in the Indonesian capital market increased significantly. The increase in new investors is also accompanied by an increase in herding behavior, as these new investors have limited experience and literacy in investing in the capital market. The sampling technique used was simple random sampling, with a total of 196 investor samples collected. The analysis method used was Structural Equation Modeling Partial Least Square. The research findings indicate that investor cognitive psychology and market information influence herding behavior among investors. However, stock characteristics do not affect herding behavior. Socio-economic factors moderate the influence of investor cognitive psychology and market information.